Latent tendencies of sexual attraction in women as a cause of coital anorgasmia - I. R. Airiyants; M. I. Yagubov (Лечащий Врач)
The article based on the analysis of the literature data substantiates the relevance of our study of 56 female patients with coital anorgasmia. In the course of the study, the authors analyzed the relationship of these disorders with latent deviations of sexual desire, characteristics of psychosexual development and erogenous reactivity of patients. The role of bi - and homosexual tendencies of the libido in the formation of the orgasmic disorder, and disharmony in a pair. The tactics of psychotherapeutic measures for this group of patients is presented.